The impact of anti-TNFα agents on weight-related changes: new insights from a real-world pharmacovigilance study using the FDA adverse event reporting system (FAERS) database. (2nd September 2021) - Mazhar, Faizan; Battini, Vera; Gringeri, Michele; Pozzi, Marco; Mosini, Giulia; Marran, Albaraa Mohammed N.; Akram, Shahzad; van Manen, Robbert P.; Radice, Sonia; Clementi, Emilio; Carnovale, Carla
ABSTRACT: Introduction: Studies in patients with immune-mediated inflammatory diseases (IMIDs) have inconsistently suggested that anti-TNFα therapy may be associated with excessive weight gain. Areas covered: We performed a nested case/non-case analysis to investigate the anti-TNF-α inhibitor-associated body-changes in the US Food and Drug Administration (FDA) Adverse Event Reporting System (FAERS) database. The risk was expressed as a measure of disproportionality using the reporting odds ratio (ROR) while adjusting for sex, drugs known to cause weight gain and reporter type. We also performed a time-to-onset (TTO) analysis of body weight-related events. Results: Infliximab was the most commonly involved TNF-α inhibitor in body weight-related changes, reaching an aROR of 1.42 (95%CI:1. 26; 1.59). An increased risk was especially found in patients affected by rheumatic disorders, both in the adult and pediatric population. The median TTO after the start of anti- TNFα therapy was about 6–7 months for both children and adults. Conclusions: Given the potential effect of these agents on the excess weight gain in IMIDs patients, continuous attention for this side effect with appropriate counseling regarding lifestyle modifications are warranted, especially in those at high risk for obesity.